Answer:
The function rule in slope-intercept form is:
![y = \frac{1}{2}x-\frac{7}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B7%7D%7B2%7D)
Step-by-step explanation:
The slope-intercept form of a function is given as:
![y = mx+b](https://tex.z-dn.net/?f=y%20%3D%20mx%2Bb)
Here
m is the rate of change of function and b is the y-intercept
The rate of change is calculated as:
![m = \frac{difference\ in\ y}{difference\ in\ x}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bdifference%5C%20in%5C%20y%7D%7Bdifference%5C%20in%5C%20x%7D)
For this, any two pairs of input and output can be taken.
So using the pairs (1,-3) and (2,-1)
![m=\frac{2-1}{-1+3}\\=\frac{1}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B2-1%7D%7B-1%2B3%7D%5C%5C%3D%5Cfrac%7B1%7D%7B2%7D)
Putting the value of slope in slope-intercept form
![y = \frac{1}{2}x+b](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx%2Bb)
Putting (1,-3) in the equation
![-3 = \frac{1}{2}(1)+b\\-3 = \frac{1}{2}+b\\b = -3-\frac{1}{2}\\b = \frac{-6-1}{2}\\b= \frac{-7}{2}](https://tex.z-dn.net/?f=-3%20%3D%20%5Cfrac%7B1%7D%7B2%7D%281%29%2Bb%5C%5C-3%20%3D%20%5Cfrac%7B1%7D%7B2%7D%2Bb%5C%5Cb%20%3D%20-3-%5Cfrac%7B1%7D%7B2%7D%5C%5Cb%20%3D%20%5Cfrac%7B-6-1%7D%7B2%7D%5C%5Cb%3D%20%5Cfrac%7B-7%7D%7B2%7D)
Putting the value of b
![y = \frac{1}{2}x-\frac{7}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B7%7D%7B2%7D)
Hence,
The function rule in slope-intercept form is:
![y = \frac{1}{2}x-\frac{7}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B2%7Dx-%5Cfrac%7B7%7D%7B2%7D)